The Effect of Reading Corner in Improving Students’ Vocabulary Grade XI MAN Binjai - Sholihatul Hamidah Daulay (VISION, 2018)
This research was intended to find out the empirical evidence of the students’ achievement by using reading corner media in improving students vocabulary grade XI MAN Binjai. This research was quantitative research. The population of this research was the students in grade XI MAN Binjai. The sample of this research were taken from 25 students of experimental group (XI-MIA 1) and 25 students of control group (XI-MIA 2). The instrument for collecting data was a test. After analyzed the data, the writer got; (1) The students improvement in vocabulary by using reading corner media got the mean 91.80 and standard deviation was 6.60. (2) The students improvement in vocabulary without using reading corner media got the mean 76,20 and standard deviation was 8.33.  The value of ttest was 7.344 and ttable was 2.011. So, the ttest was higher than ttable. It means that there was significant effect of using Reading Corner Media on students’  improvement in vocabulary.Keywords: Reading Corner, Students Vocabulary